ANALISIS PEMBIAYAAN BERMASALAH PADA BANK SYARIAH - Muhammad Fauzi; Sugianto Sugianto (Muttaqien, 2024)
The banking world is an institution that has a function and role in a nation-building effort. When talking about Islamic benches, they are definitely associated with terms like financing and loans. The case study at KCS Bank Sumut Imam Bonjol aims to find out the method of solving credit problems in Islamic banks. This study uses a descriptive qualitative approach, which examines what the research subject experienced. This study examines KP Bank Sumut Syariah in the Imam Bonjol area and uses data collection methods such as interviews, observations, documents and literature studies. This research found that the settlement of problem financing at Islamic banks (case study of KCS Bank Sumut Imam Bonjol) went smoothly and was able to resolve problem financing. We can see this in how KCS Bank Sumut Imam Bonjol has revamped the customer's installment calendar by checking their payment ability, payment desires, business prospects, and positive behavior. In addition, the KCS Bank Sumut Imam Bonjol conducted an auction for collateral which basically had a mutual agreement between the customer and the KCS Bank Sumut Imam Bonjol.